2019
DOI: 10.1002/cbic.201900341
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Self‐Assembly Studies of a Suite of Monodisperse, Facially Amphiphilic, Protein–Dendron Conjugates

Abstract: The custom design of protein–dendron amphiphilic macromolecules is at the forefront of macromolecular engineering. Macromolecules with this architecture are very interesting because of their ability to self‐assemble into various biomimetic nanoscopic structures. However, to date, there are no reports on this concept due to technical challenges associated with the chemical synthesis. Towards that end, herein, a new chemical methodology for the modular synthesis of a suite of monodisperse, facially amphiphilic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…[43] The size and molecular weight of this protein nanoparticle closely match the size of naturally occurring viral capsids. [43] Although extremely powerful, one of the significant limitations of our previous study is that the custom-designed protein assemblies are static, and they failed to exhibit dynamic behavior. This is a severe limitation considering most of the naturally occurring protein complexes exhibit dynamic behavior.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…[43] The size and molecular weight of this protein nanoparticle closely match the size of naturally occurring viral capsids. [43] Although extremely powerful, one of the significant limitations of our previous study is that the custom-designed protein assemblies are static, and they failed to exhibit dynamic behavior. This is a severe limitation considering most of the naturally occurring protein complexes exhibit dynamic behavior.…”
Section: Introductionmentioning
confidence: 76%
“…In a very recent study, we have shown that MAPLab technology can be used for the design of challenging monodisperse well‐defined protein‐dendron bioconjugates [43] . The size and molecular weight of this protein nanoparticle closely match the size of naturally occurring viral capsids [43] . Although extremely powerful, one of the significant limitations of our previous study is that the custom‐designed protein assemblies are static, and they failed to exhibit dynamic behavior.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, it is important to develop a general methodology that can incorporate a wide range of chemical entities onto the self-assembling proteins without compromising salient features of natural proteins such as a single chemical entity and the presence of well-defined functional groups in the 3d-space. Toward that goal, our group invented a new method called 'Micelle-Assisted Protein Labeling Technology (MAPLabTech) [22][23][24][25][26] . During the last several years, we have utilized MAPLabTech for the design of different families of well-defined monodisperse globular SAPs which include protein amphiphiles 22 , protein-dendron conjugates 23 , protein-peptides conjugates 24 , photo-responsive protein amphiphiles 22 , multi-responsive protein-dendron conjugates 25 , and redox-sensitive protein conjugates 26 .…”
Section: Introductionmentioning
confidence: 99%